Intervensi Gizi dan Edukasi Kesehatan Ibu Balita sebagai Strategi Penanggulangan Stunting di Desa Kembangarum - Alfina Rahmatika; Abhista Narra Mahardika; Havivi Rizki Pratama; Sintya Ulfa; Marita Mutiara; Irma Istiariani; Nabila Khoirunnisa; M. Randy Maulana Hakim (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Stunting remains a major health problem in Indonesia because it impacts child growth and the quality of human resources. Kembangarum Village, Mranggen District, Demak Regency, is an area with a relatively high prevalence of stunting. This community service activity aims to assess nutritional interventions and health education for mothers of toddlers as a strategy to overcome stunting. The community service method was carried out through collaboration between KKN UIN Walisongo Semarang students and Posyandu cadres, including the Provision of Supplementary Feeding (PMT) and balanced nutrition education through direct practice and interactive discussions. The results of the activity showed increased maternal involvement in managing nutrition and child development, as well as changes in healthier eating behaviors during the first 1,000 days of life. This intervention also strengthened social support between cadres, students, and the community. This community service activity is important as a cross-sectoral collaborative effort to reduce stunting and improve children's quality of life.